2020
DOI: 10.1016/j.jmps.2019.103826
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fields at the tip of sub-Rayleigh and supershear frictional rupture fronts

Abstract: The onset of frictional motion at the interface between two distinct bodies in contact is characterized by the propagation of dynamic rupture fronts. We combine friction experiments and numerical simulations to study the properties of these frictional rupture fronts. We extend previous analysis of slow and sub-Rayleigh rupture fronts and show that strain fields and the evolution of real contact area in the tip vicinity of supershear ruptures are well described by analytical fracture-mechanics solutions. Fractu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Beyond Cf=CSsoft, the exponent q changes dramatically with C f (Figure 9). This behavior is qualitatively similar to the characteristic form of supershear ruptures within homogeneous interfaces (Broberg, 1989; Svetlizky et al., 2020), although predicted values of q are, quantitatively, quite different. Dynamically reduced contact area only occurs at the tips of negatively propagating supershear ruptures (Figure 8).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Beyond Cf=CSsoft, the exponent q changes dramatically with C f (Figure 9). This behavior is qualitatively similar to the characteristic form of supershear ruptures within homogeneous interfaces (Broberg, 1989; Svetlizky et al., 2020), although predicted values of q are, quantitatively, quite different. Dynamically reduced contact area only occurs at the tips of negatively propagating supershear ruptures (Figure 8).…”
Section: Discussionsupporting
confidence: 69%
“…We note that the values of the wave speeds may shift slightly as a result of the finite width of our experimental samples. Recent studies of supershear ruptures within homogeneous interfaces (Svetlizky et al, 2020) have indeed demonstrated that effects due to finite sample thickness can increase longitudinal wave speeds by 3-4%. This shift toward higher velocities is consistent with the ∼4% shift of the experimentally observed supershear velocities above predicted values.…”
Section: 1029/2020jb019829mentioning
confidence: 99%
See 1 more Smart Citation
“…While proportionality of friction to normal load is mostly valid, the friction coefficient is geometry-dependent and thus varies for different experimental setups with the same material pair (Ben-David and Fineberg, 2011). The underlying cause for this observation is the mechanism governing the onset of frictional sliding, which has been shown to be a fracture-like phenomenon (Svetlizky and Fineberg, 2014;Svetlizky et al, 2020;Rubino et al, 2017). The geometry and deformability of the solids lead to a non-uniform stress state along the interface.…”
Section: Introductionmentioning
confidence: 99%

Stochastic Properties of Static Friction

Albertini,
Karrer,
Grigoriu
et al. 2020
Preprint
Self Cite
“…We study the amplitude of the speed jumps as the crack crosses the interface between regions of different toughness and show that it stems from rate-dependency of fracture energy in both phases in addition to inertia of the medium. Rate-dependent effects -features that result from the non-equilibrium nature of fracture problems and that are generally neglected [17,18] -however, significantly affect the effective toughness of periodic heterogeneous materials. Overall, our experimental observations show that as soon as non-smooth material heterogeneities are concerned, the description of fracture as an equilibrium phenomenon is too limited, and rate dependency must be taken into account.…”
mentioning
confidence: 99%